FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN KONSUMEN DALAM PEMBELIAN ONLINE (E-COMMERCE) PADA APLIKASI SHOPEE - Nurfitri Andayani (Jurnal Inovasi Teknik Informatika, 2021)
This study aimed to identify and analyze the factors that influence consumer’s online buying decisions (e-commerce) on disdus.com. The variables that were used in this study trust, safety, price, product diversity and performance risks. The data used in this study was primary data. The primary data collection was done by distributing a set of questionnaire to the users of disdus.com in Indonesia. The total of respondents were 120 respondents. The respondents were the people who fulfilled the characteristics. This study used purposive sampling method which the samples were selected strictly based on the criteria of the study.This study used the results of the IBM Statistical calculations Package for the Social Science (SPSS) version 19.0 which aimed to determine the significant level and the relationship between the dependent and independent variables. The results from the regression equation showed that there was significant influence between the variables: trust ( X1 ), security ( X2 ), price (X3), the diversity of products (X4) and performance risk (X5) toward online buying decision or e-commerce (Y). From the result of Adjusted R Square, it can be concluded that the trust variable (X1), security (X2), price (X3), the products diversity (X4), and performance risks (X5) had a simultaneous effect on the online buying decision (Y) 92.4 %. The remaining percentage namely 7.6 % (100 % - 92.4 %) was caused by the presence of other variables outside the model. Finally, the result of this study is expected to have benefit for website users. It is also expected that disdus.com pay more attention to the factors that influence online buying decision (e-commerce).